Pemilihan Prioritas Strategi Pemasaran Untuk Meningkatkan Penjualan dengan Menggunakan Metode Swot dan Topsis - ALJAHRA, DZAKIRA; Anggela, Pepy; Wahyudi, Tri (Universitas Muhammadiyah Sorong, 2025)
UMKM XYZ is a culinary business producing serundeng from grated coconut with traditional spices. The marketed products are limited to two flavor variants, lacking innovation in product variety and packaging. Sales data from 2023 indicate fluctuations between production and sales due to suboptimal marketing strategies, particularly in digital platform utilization. Therefore, an effective marketing strategy is needed to boost sales. SWOT analysis is used to identify internal and external business factors, then processed using the TOPSIS method to determine the best strategy priority. The analysis results place UMKM XYZ in Quadrant I with a Strength-Opportunity (SO) strategy, enabling optimal utilization of internal strengths and external opportunities. The TOPSIS method ranks Strategy V1 as the top priority (0.58832), which involves distributing products to major cities in Indonesia and expanding distribution channels through e-commerce. Strategy V4 ranks second (0.58420), followed by V3 (0.53041) and V2 (0.52802). Implementing these strategies is expected to enhance UMKM XYZ’s competitiveness and sales performance.